Objective burn scar assessment in clinical practice using the Cutometer: introduction and calidation of a standardized measurement protocol - Klimitz, Felix; Neubauer, Hubert; Stolle, Annette M.; Ripper, Sabine; Däschler, Simeon C.; Aman, Martin; Böcker, Arne Hendrik; Thomas, Benjamin; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of burn care & research, 2023)
An objective burn scar assessment is essential to informed therapeutic decision-making and to monitor scar development over time. However, widely employed scar rating scales show poor inter-rater reliability. For this study we developed a standardized measurement protocol for the Cutometer© applicable for objective burn scar assessment in everyday clinical practice. ...